ELT lecturers’ communicative language teaching approach in directing students’ emotions in distance learning - I Ketut Wardana; Putu Ayu Paramita Dharmayanti; Anak Agung Putu Arsana (Universitas Syiah Kuala, 2022)
The study investigated whether, and how, Communicative Language Teaching Approaches (CLTA) significantly influenced students’ academic emotions and achievement in self-directed distance learning. The participants were 76 university students in Denpasar. The data were collected through exam results and two questionnaires. Questionnaire A measured students’ learning intentions, self-encouragement, and motivation, while questionnaire B was the DASS 21. Pearson Correlation was used to analyze the effect of CLTA on student learning intention and performance, and their perception of depression, anxiety, and stress. Descriptive analysis was also performed to examine the students’ levels of negative emotions toward their academic experience. The quantitative results showed a significantly positive correlation between lecturers’ content-based instruction (CBI) and learning intention, rob (0.536) rcv (0.226); lecturers’ communicative language teaching (CLT) correlated positively with learning encouragement, rob (0.655) rcv (0.226); and lecturers’ task-based language teaching (TBLT) correlated positively with motivation, rob (0.671) rcv (0.226). This means that the CLTA strategy strongly and positively encouraged students to study and decreased the students' experiences of negative emotions. The study revealed that the more intensively the CLTA is applied, the fewer students feel depressed, and the better the students’ achievement is. The study suggests that CLTA activates affective, cognitive, and conative norms even in online learning environments.